The JFC Swing tutorial : a guide to constructing GUIs - Walrath, Kathy; Walrath, Kathy (Java series., 2004)
The JFC Swing Tutorial is back, fully revised and updated to include the latest revisions to the JFC Swing API and the Java™ 2 platform. In this book, authors and Java experts Kathy Walrath, Mary Campione, Alison Huml, and Sharon Zakhour-working closely with the Sun Microsystems Swing team-explore the ins and outs of creating GUIs with Swing components. This task-oriented, example-driven tutorial allows you to create user interfaces that work without change on multiple platforms, appearing and performing as well as or better than native interfaces. Leveraging the full power of the latest edition of the Java 2 platform, the authors bring the art of GUI creation to life with content new to this edition. This includes an easy-to-use tabbed reference section, new introductory chapters, and coverage of newer features such as JSpinner, JFormattedTextField, JProgressBar, mouse wheel support, the rearchitected focus subsystem, and improved support for drag and drop. Coverage includes: Introductory material for developers getting started with Swing, including sections on basic components such as text fields, labels, and buttons, as well as on using images The latest advice from the Swing team about thread safety Advanced Swing material, including changing key bindings, manipulating the focus, using data models, and adding painting code that uses the powerful Java 2D™ API How-to discussions on using individual components and containers, including advanced components such as tables, trees, and text editors Over 150 complete, working code examples For the novice or experienced Java developer looking to create robust, powerful, and visually stunning GUIs, The JFC Swing Tutorial, Second Edition, is an indispensable tutorial and reference.